Design and Fabrication of the Novel Miniaturized Microstrip Coupler 3dB Using Stepped Impedance Resonators for the ISM Applications - Azzeddine Sardi; Jamal Zbitou; Ahmed Errkik; Mohamed Latrach (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
In this work, a novel miniaturized compact coupler using the shunt-stubs artificial transimission lines with high and low impedances is presented. Design of the proposed coupler is accomplished by modifying the length and impedance of the branch lines in the conventional structure with the planar resonators in order to achieve branch line coupler with compact size and improvement of the performances. First part of this work is focusing on the theorical study of the proposed resonators where the equations are obtained. Secondly, the proposed coupler is designed on FR4 susbtrate, and simulated by using the EM Solver (ADS from Agilent technologies and CST microwave studio) in order to operate in the ISM band. The obtained results show good agreement with the simulations and the coupler shows a good perfo6rmance in the hole bandwidth. The size of the proposed coupler is reduced around 50% compared to the conventional design. The last part conerns the fabrication and test of the proposed coupler. The measurement and simulation results are in good agreements.